2011
DOI: 10.4041/kjod.2011.41.4.288
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of the relationship between dental and basal arch forms in normal occlusion

Abstract: Objective:The purposes of this study were to evaluate the relationship between the dental and basal arch forms; to analyze their differences in the tapered, ovoid, and square arch forms in normal occlusion by using three-dimensional (3D) virtual models; and to test the hypothesis that the overjet and maxillomandibular basal arch width difference have a significantly positive correlation. Methods: Seventy-seven normal occlusion plaster casts were examined by 3D scanning. Facial axis (FA) and WALA points were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
3
0
2
Order By: Relevance
“…Ball [6] compared the relationship between dental and basal archforms in Class II Division 1 and Class I patients, and a relationship was observed between FA and corresponding WALA points in canine and molar areas (R 2 = 0.843, 0.847). However, Kim [7] reported a moderately relevant relationship in dental and basal archforms in the canine region for normal occlusion samples (r = 0.48), and these results agreed with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ball [6] compared the relationship between dental and basal archforms in Class II Division 1 and Class I patients, and a relationship was observed between FA and corresponding WALA points in canine and molar areas (R 2 = 0.843, 0.847). However, Kim [7] reported a moderately relevant relationship in dental and basal archforms in the canine region for normal occlusion samples (r = 0.48), and these results agreed with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…They concluded that the WALA ridge estimates the basal bone archform. In other several studies [7] , [8] , the WALA points also have been used to refer the basal bone arch form,proven reliable to represent the basal bone archform.…”
Section: Introductionmentioning
confidence: 99%
“…3,[9][10][11] Teknolojinin gelişmesi ile birlikte 3 boyutlu (3D) analizlerin yapılabilir olması araştırmacıların daha gerçekçi ölçümler yapabilmek üzere farklı referans noktaları kullanımlarına olanak sağlamıştır. 12,13 Çekimli ve çekimsiz sabit ortodontik tedaviler sonucu ark genişliklerinin ve uzunluklarının değiştiği bir çok çalışmada gösterilmiştir. 14,15 Bu çalışmanın amacı minimal çapraşıklık vakalarında uygulanan sabit ortodontik tedavilerde kullanılan preform ark tellerinin alt ve üst çene dental ark formu üzerine etkilerinin üç boyutlu olarak değerlendirilmesidir.…”
Section: Introductionunclassified
“…11 Points on dental casts adjacent to the mucogingival junction (ie, the WALA ridge, named for Will Andrews and Larry Andrews who made the discovery) have also been used, with significant associations reported between WALA ridge dimensions and dental arch dimensions. [12][13][14] These relations should be expected and are also spurious because the limits of the WALA ridge landmarks were dentally defined.…”
Section: Introductionmentioning
confidence: 99%